Case report: Atypical teratoid/rhabdoid tumor of the lateral ventricle in a male adolescent (case-based review and diagnostic challenges in developing countries) - Karim, Akzhol; Shaikhyzada, Kundyz; Suleimenova, Assel; Ibraimov, Bakytkali; Nurgaliev, Dair; Poddighe, Dimitri (Frontiers in Oncology, 2022)
Atypical teratoid/rhabdoid tumor is a rare and highly malignant central nervous system (CNS) embryonal neoplasm: it accounts for <2% of all pediatric CNS tumors and occurs mainly in infants and young children. The primary localization of this tumor is the posterior cranial fossa. Supratentorial and, in detail, latero-ventricular location is extremely uncommon, especially in adolescents. This tumor is characterized by rapid growth and spread in cerebrospinal fluid spread; therefore, it is characterized by a poor prognosis. Neurological signs and symptom are related the location of the tumor. The radiological features of AT/RT are nonspecific. Immunohistochemical staining for loss of INI1 expression is considered a reliable criterion for the diagnosis of this type of tumor. AT/RT has been linked to somatic and germline mutations of SMARCB1 (INI1) or rarely of SMARCA4 (BRG1) genes, both of which work as tumor suppressor genes. There is currently no validated protocol of treatment for children with AT/RT, and multimodality treatment (consisting of surgery, chemotherapy, and radiation therapy) is currently considered. In this case report, we describe a 15-year-old adolescent with an atypical teratoid/rhabdoid tumor of the left lateral ventricle. Despite the late diagnosis, the multimodal therapeutic approach provided a good outcome for our patient at 21 months of follow-up. Based on the relevant case-based review, we conclude that early diagnosis and a multimodal approach to treatment play a key role in improving the survival of patients with this diagnosis.